Left Behind?: The Status of Women in Contemporary China - Walker, Robert (Social Inclusion, 2020)
The status of women in China has deteriorated markedly since 2006 relative to other countries, according to the World Economic Forum Gender Gap Index. Taking a longer view, the position of women has greatly improved since the founding of the People’s Republic of China but, after the ‘opening up’ of the economy, the logic of the market and the legacy of patriarchy have worked to the detriment of women. After briefly reviewing trends in China’s economic, demographic and social development, this editorial follows the structure of the thematic issue in focusing on the processes which may have caused women to slip behind. Socio-economic and political factors are considered first before focusing on the impact of unprecedently large scale migration. The circumstances and experiences of women ‘left outside’ mainstream society are explored next before reflecting on the lives of women left behind in poverty.